DIGITAL PARENTING UNTUK MENUMBUHKAN ONLINE RESELIENCE PADA REMAJA - Sofiana Sofiana; Rifqi Muhammad; Enik Sartika (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this study was to determine the benefits of Digital Parenting in growing Online Resilience in Adolescents. Digital parenting is parenting by providing clear boundaries to children about what can and cannot be done when using digital devices. The role of parents in digital parenting is to provide time limits for using smartphones and provide an understanding that what is seen on social media should not be followed with the aim of teenagers being able to adapt well to the environment so that with this ability individuals are easier to filter and respond to various things that are encountered when interact with digital technology. This research uses a descriptive approach with a qualitative research type. The results of this study show that several parents have implemented digital parenting with the aim of being able to grow online resilience in adolescents. Supporting and inhibiting factors are the presence of more attention from parents and the involvement of family members. While the obstacles are teenagers who are addicted to using smartphones and social influences who want to follow trends.